Mitochondrial Dysfunction in Parkinson’s Disease: From Mechanistic Insights to Therapy - Gao, Xiao-Yan; Yang, Tuo; Gu, Ying; Sun, Xiao-Hong (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease (PD) is one of the most common neurodegenerative movement disorders worldwide. Current treatments alleviate symptoms and suppress the progression of the disease, but there is no cure. Emerging evidence indicates that mitochondrial dysfunction is closely associated with pathogenesis of sporadic and familial PD. Because dopaminergic neurons have high energy demand, cells affected by PD exhibit mitochondrial dysfunction that promotes the disease-defining the loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). The mitochondrion has a particularly important role as the cellular “powerhouse” of dopaminergic neurons. Therefore, mitochondria have become a promising therapeutic target for PD treatments. This review aims to describe mitochondrial dysfunction in the pathology of PD, outline the genes associated with familiar PD and the factors related to sporadic PD, summarize current knowledge on mitochondrial quality control in PD, and give an overview of therapeutic strategies for targeting mitochondria in neuroprotective interventions in PD.